Influence of Incision Size on Dry Eye Symptoms in the Small Incision Lenticule Extraction Procedure. Issue 1 (January 2019) - Cetinkaya, Servet; Gulmez, Mehmet; Mestan, Emine; Ucar, Fikret; Ali, Nermin
Abstract : Purpose: To evaluate the influence of incision size on dry eye symptoms in the small incision lenticule extraction (SMILE) procedure. Methods: Ninety-four eyes of 47 patients with myopia and/or myopic astigmatism who had undergone the SMILE procedure were enrolled in this study. The patients were divided into 3 groups according to the incision size (2, 3, and 4 mm) applied during the SMILE procedure. Results: There were no significant differences among the groups in respect to age and sex ( P values 0.251 and 0.974, respectively) and in respect to preoperative, postoperative first day, first week, first month, third month, and sixth month values of the Ocular Surface Disease Index score, tear break-up time, ST1, and staining grades. Conclusions: There was no difference in dry eye symptoms with 2-, 3-, and 4-mm incisions. In the learning period of SMILE surgery, larger incision sites can be used to make the procedure easier.